Estimation of Serum Urea, Creatinine and Uric Acid in Obese Subjects - A. M. Siddiqui, A. R. Shinde, Humaira N. Khan, Anjali Pergulwar (International Journal of Innovative Research in Medical Science, 2017)
Introduction - Obesity is often a neglected renal risk factor. It may play a important role in progression of renal disease. Aim and Objectives - To estimate blood urea, serum creatinine, serum uric acid in Obese and control group. Method and Material - Total 50 obese subjects and 50 controls were taken for study. Serum /plasma urea ,serum creatinine and serum uric acid was measured on fully automated XL-640 , using Erba diagnostic kits. Observation and Results - The mean values of study parameters was found to be elevated in obese group as compared to controls .Result was expressed in Mean ± S.D. Conclusion - Renal profile was altered in obese subjects with increased levels of serum/plasma urea, serum creatinine, serum uric acid.